Resident's satisfaction to relocated Houses after 2004 Indian Ocean Tsunami, Thailand - Titaya Sararit (2018)
© 2018 The Authors. Published by Elsevier Ltd. After Indian Ocean tsunami of 26 December 2004, Government, NGO and private organizations provided various types of post-disaster permanent housing. This study focuses on Relocate houses in Namkem community, Phangnga after residents live long-term in this post-disaster house. Aims to analyze resident's satisfaction to Housing after lived more than a decade in the post-tsunami houses and analyze the development to physical of house regard to reconstruction, functions, or size. The relocation effect to the house adaptation and residents life style as a result shown that even self-built house that residents have participate in design and construction process themselves also need the individual renovation, according to that many of residents have change their job or need to travel in longer distance for work, The car park was one of the popular choice for space extension follow after the adding more bedrooms as number of family member increase. Residents who individually renovated and extend the house have gain more satisfy with their house so provided land-plot for self-extension may important more for recovery housing.